Pengaruh Kualitas Pelayanan Dan Kepuasan Pelanggan Terhadap Loyalitas Nasabah Pada KSP Sada Roha Jaya Di Ranjok Kota Mataram - Dewi Berliana; Satriawan; Lalu Mimbar (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to determine the partial and simultaneous the effect of service quality and customer satisfaction partially and simultaneously on member loyalty and the variable that has the most dominant influence between service quality and customer satisfaction on member loyalty at Ksp Sada Roha Jaya in Ranjok, Mataram City. The population in this study is unknown so the sample was determined using the nonprobability sampling method and accidental sampling technique. So the number of samples determined was 100 respondents. The statistical test tool used is multiple linear regression analysis. The results of this study show that partially the variables of service quality and customer satisfaction have a positive and significant effect on member loyalty, simultaneously the variables of service quality and customer satisfaction have a significant effect on member loyalty. Furthermore, the variable that has the most dominant effect is service quality.